472. Corticosteroid Exposure as a Risk Factor for Pneumocystis jirovecii Pneumonia Mortality in HIV-Negative Patients: A Multicenter Retrospective Case-Control Study with a Global Research Network Validation. (15th December 2022) - Vargas Barahona, Lilian; Molina, Kyle C; Pedraza-Arévalo, Laura C; Sillau, Stefan; Tagawa, Alex; Scherger, Sias; Chastain, Daniel B; Shapiro, Leland; Franco-Paredes, Carlos; Hawkins, Kellie; Henao-Martínez, Andrés F
Abstract: Background: HIV-negative patients have higher mortality from PJP compared to patients with HIV, however, we lack data on predictors of PJP-associated mortality in HIV-negative patients. We aim to characterize the role of previous corticosteroid exposure in PJP-related mortality. Methods: A multicenter retrospective case-control study was performed on HIV-negative patients tested for PJP within the UCHealth system from 2000 to 2021. Cox proportional-hazards model was used for survival analysis. We queried TrinetX, a global research network, to validate mortality risk differences among HIV-negative patients with PJP with prior corticosteroid exposure versus those without. We used propensity score matching to assess independent corticosteroid risk of 1-year mortality. Results: We identified 105 cases of PJP and 71 controls without PJP. HIV-negative patients with steroid exposure in the previous 6 months were more likely to have a history of malignancy (26.5% vs 11.9%, p=0.026), solid organ transplant (14.8% vs 3.4%, p=0.023), inflammatory disease (27.6% vs 8.5%, p=0.03), or use of other immunosuppressive drugs (83.8% vs 13.6%, p< 0.0001). The median prednisone equivalent dose was higher in patients who died at 7 weeks (33.7 vs. 21.5 mg/d) and 1 year (33.7 vs. 20 mg/d). Adjusted Cox proportional-hazard model found an increased rate of death at 10 weeks (HR: 3.8, CI: 1.6-9.26, p=0.003)(Figure 1) and 1 year (HR: 4.8, CI: 2.2-10.7, p< 0.0001) among patients previously on steroids. A TrinetX-based propensity score matching of 2176 HIV-negative patients found a significantly increased 1-year mortality (OR: 1.9 CI: 1.6-2.2, p< 0.0001) after PJP diagnoses in the group with corticosteroid exposure in the previous year compared to those with PJP without corticosteroid exposure. The mean β-d-glucan (203±154 vs. 82± 35.8 pg/mL, p=0.025) and ferritin levels (1591±5576 vs. 1041± 1300 mcg/L, p=0.02) were higher in those with prior steroid use. Figure 1. Adjusted 70-days mortality among HIV negative patients with PJP by corticosteroid exposure Conclusion: HIV-negative patients with PJP and corticosteroid use preceding diagnosis have higher mortality than those without corticosteroid use. A higher fungal burden may influence corticosteroid mediated mortality. Disclosures: All Authors : No reported disclosures.